HEADMASTER LEADERSHIP IN IMPROVING STUDENT ENTREPRENEURSHIP CREATIVITY AND INNOVATION (Forum for Linguistic Studies, 2024)
This research is motivated by the low entrepreneurial competency of vocational school students, which has an impact on the lack of vocational school graduates who become entrepreneurs independently/open new job opportunities. This is because entrepreneurship education in schools has so far only touched on the level of introducing norms or values, not yet at the level of internalization and real action in everyday life. The purpose of this research is to determine and analyze the Principal's Leadership Management in increasing student creativity and Entrepreneurial Innovation. The research was conducted at SMK HKTI 2 Purwareja Klampok and SMK Al Huda Kaliabu Salaman Magelang with research subjects being principals, deputy principals, teachers and students. The policy underlying this research is Minister of National Education Regulation Number 13 of 2007 concerning Competency Standards for School/Madrasah Principals. This research is based on strategic management theory according to Thomas L Wheelen and J. David Hunger. The research method used is a case study. Research Results: 1) Vocational headmaster carry out transformational leadership characteristics, so that the principal has a high entrepreneurial ethos and can work together and mobilize the school community to create an entrepreneurial culture at school and outside school. 2) The Principal has implemented strategies to improve the quality of graduates but has not maximum. This is proven by the school only formulating the vision, mission and goals of the school, and establishing policy guidelines for achieving graduate competency, so that development, but to achieve these goals has not been outlined in the School Work Plan. 3) The implementation of entrepreneurship programs in vocational schools has been integrated with education and entrepreneurial values ​​are very high and entrenched in schools. 4) There are several obstacles for headmaster in efforts to increase student creativity and entrepreneurial innovation, including less relevant learning methods and skill competencies, less effective teaching factories, and a lack of establishing partnerships with the business world, industrial world and the world of work. 5) There are solutions to overcome obstacles for headmaster in efforts to increase student creativity and entrepreneurial innovation, including vocational school students who are required to increase teacher competency in implementing learning technology, designing curriculum and facilitating facilities and infrastructure according to business and industry standards, organizing teaching factories and establishing collaborations. with partner agencies. The conclusion of this research is that the Principal has attempted to increase student creativity and entrepreneurial innovation through various programs in the field of expertise held, but the results have not been optimal.